Specific features of development of complex-structural model of formation of meaning of life personal strategies in conditions of the armed conflict - Evgeniya N. Ryadinskaya (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Considered in the article are the features of the development of a complex structural model of the formation of meaning of life strategies of the individual in conditions of the armed conflict. The author reveals the content of the structural components of the individual's life strategies, identifies the mechanisms and levels of their formation. Particular attention is paid to the analysis of existing models of the formation of life strategies. The article traces the connection between the process of formation of life strategies with social adaptation and innovative activity of the individual. Based on the analysis of theoretical and methodological approaches, a complex structural model of the formation of meaning of life strategies of the personality in the conditions of the armed conflict in the southeast of Ukraine during the conflict and postconflict period was developed. The author proposes a general scheme of recovery areas, which presupposes activity in the political, socio-economic, socio-cultural and psychological areas, and the components of remedial work with civilians in conditions of the armed conflict (physiological, cognitive, emotional, behavioral, personal) have been established as well. The author adheres to the system and structural approach to rendering help to people in the immediate area of the armed conflict, and offers a model for restoring the personality on three levels: individual, micro-and macrosystemic, which will determine the ways and means of providing the various types of assistance required. Attention is drawn to the fact that when developing models and programs for the recovery of personality in the period of the armed conflict, it is the psychological component that should be given due consideration, for it will contribute to the effective prevention of the subsequent psychological consequences of the armed conflicts as well as to their leveling. In conclusion, the author claims that it is important to apply an integrated approach to the problem of restoring civilians at the time of the armed conflict, taking into account the political, socio-economic, socio-cultural and psychological causes and consequences of the conflict in order to effectively counter them in the future, prevent new violence, and promote the establishment of a viable peace.